2011
DOI: 10.1111/j.1747-1567.2010.00691.x
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigations of Backfill Conditions on the Performance of High-Density Polyethelene Pipes

Abstract: In this study, a series of laboratory tests on 100‐mm‐diameter high‐density polyethylene (HDPE) 100 PE flexible pipe buried in poorly graded Sile quartz sand with different relative densities are described. The laboratory tests were performed in a 40‐mm‐thick plexiglass fronted test tank that replicated a classical trench section in field conditions. The HDPE flexible pipe was positioned against the glass with its longitudinal axis perpendicular to the glass. This allowed direct observation of the backfill–pip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Von-Mises stress can be expressed by the stress component, as shown in Equation (8). Previous studies have focused on the circumferential stress and changes in the diameter of the flexible pipe to indicate the deformation of the pipe [9,16,23,51]. Compared with the real stress, the von-Mises stress comprehensively considers the deformation of materials in multiple directions, and the assessment of the ductile failure of pipes is more accurate; thus, it is reasonable to take the Von-Mises stress as a parameter that indicates the deformation of the pipe [52][53][54].…”
Section: Generalmentioning
confidence: 99%
See 1 more Smart Citation
“…Von-Mises stress can be expressed by the stress component, as shown in Equation (8). Previous studies have focused on the circumferential stress and changes in the diameter of the flexible pipe to indicate the deformation of the pipe [9,16,23,51]. Compared with the real stress, the von-Mises stress comprehensively considers the deformation of materials in multiple directions, and the assessment of the ductile failure of pipes is more accurate; thus, it is reasonable to take the Von-Mises stress as a parameter that indicates the deformation of the pipe [52][53][54].…”
Section: Generalmentioning
confidence: 99%
“…Talesnick et al (2011) designed a new technique to measure the radial contact pressure applied to a buried pipe and the deflection of the pipe under static vertical loading, and the measurement results indicated that the radial contact pressure and deflection of the pipe were sensitive to the compaction backfill [15]. Terzi et al (2012), through a series laboratory tests on HDPE pipes buried in poorly graded sand with different compaction, found that the stress and deformation of these pipes were higher when the surrounding backfill was loose, and the maximum stress appeared at the invert, whereas the crown stress and invert stress were higher when the backfill was compact [16]. In addition, the method of installation and the type of backfill material were also key factors that affected the deformation of the pipe.…”
Section: Introductionmentioning
confidence: 99%
“…(2012) buried HDPE pipes in poorly graded sand with different compaction degrees to measure the strain response of pipe to external loads. e results indicated that when the backfill around the pipe is loose, the maximum strain occurs at the invert of the pipes, and when the backfill is fully compacted, the maximum strain occurs on the crown of the pipes [20]. Brachman et al (2008) conducted laboratory experiments to compare the effects of compaction methods, backfill materials, and gradation on the deflection, strain, and local bending of special-shaped thermoplastic pipes.…”
Section: Introductionmentioning
confidence: 99%
“…High-density polyethylene (HDPE) pipe, well known as a type of thermoplastic pipe, is used instead of concrete and steel pipes for many applications, such as gas and fluid transfers, water/sewage drainages, and electrical and communication conduits (Refs. [1][2][3]. The HDPE pipe shows many excellent properties, such as light weight, chemical resistance, and tolerance for decomposition (Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Although HDPE pipe has been appropriate for underground applications, it also has high ductility and low stiffness, which causes an unstable shape when it receives highly compressive forces (Refs. 3,4). Recently, the strength of HDPE pipe has been improved by methods such as increasing the wall thickness, spiral shape designs, and reinforcements such as fiberglass and ceramic, etc.…”
Section: Introductionmentioning
confidence: 99%